Comparison of doses of heparin for venous thromboembolism and bleeding in pregnant women. (17th December 2021) - Xiao, Sha; Luo, Yuancai; Guo, Lu; Zhang, Jing; Mu, Liping; Ye, Zhao
Abstract : The evaluation criteria for dosage of low-molecular-weight heparin (LMWH) for pregnant women at high risk of venous thromboembolism (VTE) remain unclear. A retrospective study was performed to investigate the relative appropriate LMWH administration strategy and dosage for pregnant women at risk of VTE. 219 pregnant women with perinatal and postpartum VTE were reviewed and divided into group A (fixed dose group: n=73, 5000 IU dalteparin daily for all women), group B (weight group: n=73, 2500 IU dalteparin daily for women less than 50 kg; 5000 IU dalteparin daily for women more than 50 kg), and group C (anti-factor Xa (FXa) + weight group: n=73, 5000 IU once daily for women less than 50 kg; 7500 IU once daily for women weighing 50–80 kg; 10, 000 IU once daily for women weighing over 80 kg). Further dose administration was adjusted according to peak anti-FXa level, maintaining the peak at the 0.5–1.0 IU/mL range. Women in group C presented lower incidence of VTE and other pregnancy complications than group A and group B. Adjusting the dosage of LMWH according to both weight and anti-FXa level of pregnant women not only prevented VTE but also reduced the risk of postpartum hemorrhage induced by LMWH administration. In addition, adjusting the dose of LMWH according to anti-FXa level and body weight also affected the recurrence of VTE and the occurrence of postpartum hemorrhage in pregnant women.